THE EFFECT OF FIRM SIZE, CURRENT RATIO, TOTAL ASSET TRUN OVER, DEBT ASSET TO RATIO ON PROFITABILITY IN MANUFACTURING COMPANIES IN THE CONSUMER GOODS INDUSTRY SECTOR LISTED ON THE IDX IN 20219-2022 - Veronika Pandiangan; Ayang Pratama; Yeti Meliany Lubis (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to see the relationship between variables, both individually and together, with the title Influence of Firm Size, Current Ratio, Total Asset Turn Over, Debit To Asset Ratio on Profitability in consumer goods industry sector companies listed on the IDX in 2019- 2022. The method we use in this research is a quantitative method. The population of companies in the consumer goods industry sector in 2019-2022 was 31 with 22 samples. This research observation used purposive sampling with partial test (T test), simultaneous test (F test), classical assumption test, and R square test. The test results for this observation are Firm Size, Current ratio, Total Asset Over, and Debit to Asset Ratio, which have a significant effect on Return On Equity. With an R squere result of 41.8% and influenced by other variables of 58.2%. So the results of the overall Firm Size, Current Ratio, Total Asset Trun Over, Debit to Asset Ratio have a simultaneous effect on companies in the consumer goods industry sector listed on the Indonesian Stock Exchange in 2019-2022